Packaging of organic food—the dilemma of consumers’ internal and external motives - Nifatova, Olena; Bliumska-Danko, Kseniia; Charreire-Petit, Sandra; Danko, Yuriy (Frontiers in Sustainability, 2025)
This study provides empirical insights to clarify consumers’ motives for choosing organic food and the importance of the packaging of organic food in shaping consumers’ perceptions of food organicity. Based on a survey of 497 consumers of organic food in Ukraine, we investigate the extent to which organic packaging can serve as an indicator of external (altruistic) consumers’ expectations and whether the environmental friendliness of consumer choice is related to their expectations of sustainability (greenness) of organic food at all stages of their life cycle. We have found that there is no clear distinction between internal and external consumer motives in the perception of food organicity due to the perception of packaging organicity as part of food organicity. However, organic packaging can be an indicator of external (altruistic) consumer motives, subject to the limitations that organic packaging is less related to health care and more to altruistic motives. Consumers driven by external motives may expect produce to be organic at all stages of their life cycle and are more likely to rely on the producer’s commitment to environmental responsibility. Organic producers should consider this in their marketing strategies to meet consumer expectations and avoid the risk of greenwashing. Our results can serve as a starting point for further exploration of ways to foster mutual understanding between consumers and producers regarding shared environmental responsibility.